Questões políticas na comédia declamada brasileira: 1837-1938 - Ferreira, Adriano de Assis (2012)
The objective is the analysis of political issues present in seven Brazilian comedies declaimed, represented between 1837 and 1938: O Juiz de Paz da Roça, Torre em Concurso, Como se Fazia um Depuado, Caiu o Ministério!, Ministro do Supremo, O Secretário de Sua Excelência, Fora da Vida. Rationale: such issues resonate in the present, explaining the peculiarities of Brazilian political life. Hypothesis: the presence of officials of dubious morality in the first six pieces depicts an environment of patronage and clientelism that affect the exercise of state functions, the last part presents an official morally suitable, but the problems stem from an unjust legality. Methodology: critical reading of the plays, noting the confluence between art and politics. Result: confirmation of the hypothesis